2018
DOI: 10.3389/fnins.2018.00113
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-Motor Control of Vocal Production during Divided Attention: Behavioral and ERP Correlates

Abstract: When people hear unexpected perturbations in auditory feedback, they produce rapid compensatory adjustments of their vocal behavior. Recent evidence has shown enhanced vocal compensations and cortical event-related potentials (ERPs) in response to attended pitch feedback perturbations, suggesting that this reflex-like behavior is influenced by selective attention. Less is known, however, about auditory-motor integration for voice control during divided attention. The present cross-modal study investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Current theories of language production consider a feedback monitoring system that monitors speech output to correct errors during production (for reviews, see Hickok, 2012; Houde and Chang, 2015). Evidence about the importance of such a system comes from adaptations of the speaker’s speech output to compensate for sensory (i.e., auditory and somatosensory) feedback manipulations (Bauer et al, 2006; Burnett et al, 1998; Guo et al, 2017; Houde, 1998; Liu et al, 2018; Shiller et al, 2009; Tremblay et al, 2003). But such feedback monitoring system cannot account for extremely fast self-corrections of speech observed in humans (Blackmer and Mitton, 1991; Nozari et al, 2011), as they require extended neural processing time.…”
Section: Introductionmentioning
confidence: 99%
“…Current theories of language production consider a feedback monitoring system that monitors speech output to correct errors during production (for reviews, see Hickok, 2012; Houde and Chang, 2015). Evidence about the importance of such a system comes from adaptations of the speaker’s speech output to compensate for sensory (i.e., auditory and somatosensory) feedback manipulations (Bauer et al, 2006; Burnett et al, 1998; Guo et al, 2017; Houde, 1998; Liu et al, 2018; Shiller et al, 2009; Tremblay et al, 2003). But such feedback monitoring system cannot account for extremely fast self-corrections of speech observed in humans (Blackmer and Mitton, 1991; Nozari et al, 2011), as they require extended neural processing time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multivariate logistic regression analysis revealed a lower educational level as an independent risk factor for PD-associated MSD. Several studies on the neural mechanisms underlying motor speech control [15, 16, 26, 27] have hypothesized that a higher educational level might play a negative role in the occurrence and aggravation of PD-associated MSD. Previous MRI examinations have shown that lesions in cognitive-relevant cortical areas, especially those closely associated with educational level within the prefrontal lobe, frequently occur in SD patients [2830].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multivariate logistic regression analysis revealed a lower educational level as an independent risk factor for PD-associated MSD. Several studies on the neural mechanisms underlying motor speech control [15,16,26,27] have hypothesized that a higher educational level might play a negative role in the occurrence and aggravation of PD-associated MSD. Previous MRI examinations have shown that lesions in cognitiverelevant cortical areas, especially those closely associated with educational level within the prefrontal lobe, frequently occur in SD patients [28][29][30].…”
Section: Discussionmentioning
confidence: 99%